Baseline quality of life and chemotherapy toxicities in patients with early breast cancer. Issue 7 (15th January 2023) - Licaj, Idlir; Coquan, Elodie; Dabakuyo‐Yonli, Tienhan Sandrine; Dauchy, Sarah; Vaz Luis, Ines; Charles, Cecile; Lemogne, Cedric; Tredan, Olivier; Vanlemmens, Laurence; Jouannaud, Christelle; Levy, Christelle; Rigal, Olivier; et al.
Abstract: Background: The authors used the French breast cancer Cancer and Toxicities (CANTO) cohort to study the associations between baseline quality of life and chemotherapy dose‐reductions (CDRs) or postchemotherapy‐toxicities (PCTs). Methods: In total, 3079 patients with breast cancer who received chemotherapy were included in this analysis. The associations between baseline physical functioning (PF) and fatigue measured using the European Organization for Research and Treatment of Cancer Quality‐of‐Life Questionnaire Core 30, and two endpoints—CDRs during adjuvant or neoadjuvant chemotherapy; and selected PCTs were estimated with odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) using logistic regression models. Results: Among the 3079 patients from the CANTO cohort who were included, 718 (33.0%) received chemotherapy in the neoadjuvant setting, and 2361 (67.0%) received chemotherapy as adjuvant treatment. The chemotherapy included taxanes in 94.2% of patients and anthracyclines in 90.5% of patients. Overall, 15.5% of patients experienced CDRs and, 31.0% developed PCTs. Women with low baseline PF scores (<83) had higher multivariate odds of developing CDRs compared with those who had PF scores ≥83 (OR, 1.54; 95% CI, 1.13–2.09). The corresponding OR for PCTs was 1.50 (95% CI, 1.13–2.00). Women with high baseline fatigue scores had higher odds of CDRs (OR, 1.43; 95% CI, 1.13–1.76) and PCTs (OR, 1.32; 95% CI, 1.10–1.59). Conclusions: By using the national CANTO cohort, baseline PF and fatigue were independently associated with CDRs and PCTs. Abstract : In the French national breast cancer Cancer and Toxicities cohort, the authors observed that baseline physical functioning and fatigue scores were independently associated with chemotherapy dose reductions and chemotherapy‐induced toxicities.